Differences in Expulsion on Post-placenta Intrauterine Contraceptive Device between Mother with Vaginal and Cesarean Delivery - Atika Zahria Arisanti; Tono Djuwantono; Sri Endah Rahayuningsih (Universitas Islam Bandung, 2020)
Intrauterine device (IUD) is a long term, highly effective, and reversible contraception method. In Indonesia, the number of IUD acceptors is still lower than other methods. An effort to improve the long term contraception is using post-placental IUD that can be a choice for postpartum mother who has limited access to another contraception service. The purpose of this study was to compare the incidence of expulsion in post-placental IUD insertion between mother with vaginal delivery and cesarean delivery. This study design was a comparative cross-sectional method with a consecutive sampling technique conducted at Dr. Hasan Sadikin General Hospital Bandung and Dr. Kariadi General Hospital Semarang from November 2017 to February 2018. Subjects were postpartum mothers who received post-placental IUD insertion at vaginal delivery and cesarean delivery. Samples were 96 women, consisting of 48 women with IUD insertion in vaginal delivery and 48 women with IUD insertion in cesarean delivery. Data obtained from interviews and transvaginal ultrasonography examination. The result showed there was a difference in expulsions incidence between IUD’s insertion among vaginal delivery compared to cesarean delivery (p=0.041). It concluded that expulsion’s to post-placental IUD insertion is higher in vaginal delivery compared to cesarean delivery. PERBEDAAN KEJADIAN EKSPULSI PADA PEMASANGAN ALAT KONTRASEPSI DALAM RAHIM PASCAPLASENTA ANTARA IBU DENGAN PERSALINAN PER VAGINAM DAN PERSALINAN SECTIO CAESAREAAlat kontrasepsi dalam rahim (AKDR) merupakan kontrasepsi jangka panjang, efektif dan reversibel. Di Indonesia, jumlah akseptor AKDR masih lebih rendah daripada metode lainnya. Salah satu upaya untuk meningkatkan penggunaan kontrasepsi jangka panjang, yaitu dengan AKDR pascaplasenta yang dapat menjadi alternatif bagi ibu pascasalin yang mempunyai akses terbatas untuk mendapatkan pelayanan kontrasepsi. Penelitian ini bertujuan membandingkan kejadian ekspulsi pada pemasangan AKDR pascaplasenta antara ibu dengan persalinan per vaginam dan persalinan sectio caesarea. Desain penelitian ini adalah cross-sectional komparatif dengan teknik pengambilan sampel consecutive yang dilaksanakan di RSUP Dr. Hasan Sadikin Bandung dan RSUP Dr. Kariadi Semarang dari bulan November 2017 hingga Februari 2018. Subjek penelitian adalah ibu pascasalin yang mendapatkan insersi AKDR pascaplasenta pada persalinan per vaginam dan persalinan sesar. Jumlah sampel 96 ibu, terdiri atas 48 ibu yang bersalin per vaginam dan 48 ibu yang bersalin sesar. Data didapatkan melalui wawancara dan pemeriksaan ultrasonografi transvaginal. Hasil penelitian menunjukkan terdapat perbedaan kejadian ekspulsi pada pemasangan AKDR antara ibu dengan persalinan per vaginam dan persalinan sectio caesarea (p=0,041). Simpulan, kejadian ekspulsi pada pemasangan AKDR pascaplasenta lebih tinggi pada ibu dengan persalinan per vaginam dibanding dengan persalinan sectio caesarea.